Generalized compensation principle - Karl Schulz; Aleh Tsyvinski; Nicolas Werquin (Theoretical Economics, 2023)
Economic disruptions generally create winners and losers. The compensation problem consists of designing a reform of the existing income tax system that offsets the welfare losses of the latter by redistributing the gains of the former. We derive a formula for the compensating tax reform and its impact on the government budget when only distortionary tax instruments are available and wages are determined endogenously in general equilibrium. We apply this result to the compensation of robotization in the U.S.
Keywords: H21; H31; D61; D63; 330; Compensation principle; distortionary taxation; general equilibrium; wage disruption